Comparing the effects of different dynamic sitting strategies in wheelchair seating on lumbar-pelvic angle. Issue 1 (December 2016) - Li, Chun-Ting; Peng, Yao-Te; Tseng, Yen-Ting; Chen, Yen-Nien; Tsai, Kuen-Horng
Abstract Background Prolonged static sitting in a wheelchair is associated with an increased risk of lower back pain. The wheelchair seating system is a key factor of this risk because it affects spinal loading in the sitting position. In this study, 7 dynamic sitting strategies (DSSs) are examined: lumbar prominent dynamic sitting (LPDS), back reclined dynamic sitting (BRDS), femur upward dynamic sitting (FUDS), lumbar prominent with back reclined dynamic sitting (LBDS), lumbar prominent with femur upward dynamic sitting (LFDS), back reclined with femur upward dynamic sitting (BFDS), and lumbar prominent with back reclined with femur upward dynamic sitting (LBFDS). The objective of this study was to analyze the biomechanical effects of these sitting strategies on lumbar-pelvic angles. Methods Twenty able-bodied participants were recruited for the study. All participants performed LPDS, BRDS, FUDS, LBDS, LFDS, BFDS, and LBFDS in a random order. All lumbar-pelvic angle parameters, including the static lumbar angle, static pelvic angle, lumbar range of motion, and pelvic range of motion were measured and compared. Results Results show that LBDS and LBFDS enabled the most beneficial lumbar movements, although the difference between the 2 strategies was nonsignificant. BRDS and BFDS enabled the most beneficial pelvic movements, although the difference between the 2 strategies was nonsignificant. Among all the upright DSSs, LPDS and LFDS enabled the most beneficial lumbar and pelvic movements, although no significant difference was observed between these 2 strategies. Conclusions We identified the effects and differences among 7 DSSs on lumbar-pelvic angles. Wheelchair users can choose the most suitable DSS that meets their needs. These findings may serve as a reference for practicing physicians or wheelchair users to choose an appropriate dynamic wheelchair seating system. Trial registration ISRCTN12389808, 18th November 2016, retrospectively registered.